A genome-wide transcriptomic analysis of embryos fathered by obese males in a murine model of diet-induced obesity - Bernhardt, Laura; Dittrich, Marcus; El-Merahbi, Rabih; Saliba, Antoine-Emmanuel; Mueller, Tobias; Sumara, Grzegorz; Vogel, Joerg; Nichols-Burns, Stefanie; Mitchell, Megan; Haaf, Thomas; El Hajj, Nady (Scientific Reports, 2021)
Paternal obesity is known to have a negative impact on the male's reproductive health as well as the health of his offspring. Although epigenetic mechanisms have been implicated in the non-genetic transmission of acquired traits, the effect of paternal obesity on gene expression in the preimplantation embryo has not been fully studied. To this end, we investigated whether paternal obesity is associated with gene expression changes in eight-cell stage embryos fathered by males on a high-fat diet. We used single embryo RNA-seq to compare the gene expression profile of embryos generated by males on a high fat (HFD) versus control (CD) diet. This analysis revealed significant upregulation of the Samd4b and Gata6 gene in embryos in response to a paternal HFD. Furthermore, we could show a significant increase in expression of both Gata6 and Samd4b during differentiation of stromal vascular cells into mature adipocytes. These findings suggest that paternal obesity may induce changes in the male germ cells which are associated with the gene expression changes in the resulting preimplantation embryos.
CRIS-Team WoS Importer:2021-03-12